Democracy and Human Rights in Africa : The Politics of Collective Participation and Governance in Cameroon - Fossungu, Peter Ateh-Afac (Book collections on Project MUSE., 2013)
Since the mid-1980s, there has been much federalism talk in Cameroon where federation (said to have been created in Foumban in 1961) had supposedly been 'overwhelmingly' rejected in 1972 by Cameroonians. 'Confusioncracy' is the one good term that could conveniently explain it. Written with the trilogy of criticism, provocation, and construction in mind, this book aims at reconstructing a new and vigorous society in Cameroon that ensures respect for fundamental human rights and certain basic shared values. Much as the book centres on the Anglophone Problem; it is principally about human rights and their excessive violations - the direct result of the absence of separation of powers and constitutionalism. It largely condemns Cameroon's government for incessantly singing democracy and rule of law at the same time as it is massively torturing and wantonly killing citizens that dare to question the confusion. While sharing the position that a state like Cameroon must be seen to ensure that its laws and other practices accord with its international commitments, the book nonetheless strives to apportion the blame for Cameroon's human rights catastrophe accordingly; showing how the English-speaking minority itself, generally speaking, contributes to a large extent in propping up the dictatorship that is oppressing not only that minority but Cameroonians at large. The book challenges Cameroon to assume a leadership role in uniting Africans through meaningful federalization rather than further splitting them into incapable mini-states on the challenging world stage.